Children with cavernous malformations of the central nervous system. (November 2021) - Arkar, Ula; Vipotnik Vesnaver, Tina; Maver, Aleš; Perković Benedik, Mirjana; Peterlin, Borut; Osredkar, Damjan
Abstract: Background: Cavernous malformations (CM) of the central nervous system (CNS) are a rare pathology in the pediatric population that may present with an acute onset of severe neurological symptoms. Objective: The aim of our study was to evaluate the clinical presentation, family history, genetic background, radiological features, treatment and outcome of children with CM. Methods: This observational cohort study included all children with CM of the CNS diagnosed in the period 2000–2020 at University Children's Hospital in Ljubljana, Slovenia. Whole exome sequencing was utilized. Results: We identified a cohort of 20 children with CM (mean age 9.3 years, range: 10 days–18.4 years). In our cohort, 16 patients were symptomatic and 4 were asymptomatic; 7 patients had a solitary lesion, and 13 had multiple lesions. Children with multiple lesions become symptomatic at an earlier age compared with children with solitary lesions. We identified five families with familiar cavernous malformation (FCM) syndrome affecting two or more generations; FCM represented 65% of all pediatric cases identified in our study. We confirmed a mutation in FCM associated genes in all but one patient with multiple lesions, with the KRIT1 mutation being the most common. Conclusion: Multiple CM lesions and symptomatic brainstem lesions are associated with worse neurological deficits in pediatric patients. Not all cases of multiple lesions can be linked to mutations in KRIT1, CCM2, or PDCD10, which may indicate that there are other as yet unidentified genes associated with FCM. Highlights: Cavernous malformations (CM) present a rare pathology in the pediatric population. Multiple CM and symptomatic brainstem lesions are associated with worse deficits. Active screening should be performed in families of children with multiple CM. Not all cases of multiple CM can be linked to mutations in KRIT1, CCM2, or PDCD10.